Prevalence of hypertension and its associated factors among university staff - Gyanchand Rampal, Lekhraj Rampal; Bezenjani, Somayeh Aminizadeh; Md Said, Salmiah; Ibrahim, Faisal; Syed Yahya, Sharifah Zainiyah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Introduction: In Malaysia, cardiovascular diseases (CVD) have been the leading cause of death for the past 40 years. Hypertension is the leading treatable risk factor for CVD mortality. Objectives: To determine the prevalence and factors associated with hypertension among University Putra Malaysia staff. Methods: A Cross sectional study design was used in this study. The sample was selected using table of random numbers. Two blood pressure measurements were taken from respondents aged 30 years and above. Data on socio-demographic variables and lifestyle-related risk factors were collected using a pre-tested structured questionnaire. Weight and height measurements were also taken. Results: Out of 517 respondents selected, 454 subjects agreed to participate, giving a response rate of 87.8%. The overall mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) for 454 respondents was 126.2 mmHg and 80.17 mmHg respectively. The mean SBP was significantly higher in males (129.68 mmHg) as compared to the females (122.65 mmHg). The mean SBP and DBP significantly increased with age in both males and females (p<0.05). There was a significant relationship between SBP and BMI (r = 0.55, r2= 0.30 p <0.001) and diastolic blood pressure and BMI (r= 0.53, r2=0.28, p<0.001). The overall prevalence of hypertension was 34.4% and 33.9% had pre hypertension. Hypertension was significantly associated with age, gender, family history of hypertension, BMI and alcohol consumption. Conclusions: Prevalence of hypertension and pre-hypertension is high. There is an urgent need for implementation of a comprehensive CVD prevention program. Routine blood pressure measurements should be taken to improve the detection, prevention and treatment of hypertension.